2012
DOI: 10.2139/ssrn.2010476
|View full text |Cite
|
Sign up to set email alerts
|

Who Benefits from Removing User Fees for Health Care? Evidence from a Randomised Experiment in Ghana

Abstract: The extent to which removing user fees for health care in developing countries improves population health rests, in part, on how behavioural responses vary across individuals with different health needs. Using data from a randomised experiment of free care in Ghana and a measure of baseline health that is both objective and broad-based, we examined differential effects for initially ill and healthy children. We find that free care improved health seeking behaviour, lowered out-of-pocket spending and reduced an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The results of this study are consistent with Asuming's (2013) findings, which suggested that poorer households have larger unmet needs for health services and are more responsive to interventions. Similarly Powell-Jackson et al (2014) found that the effect of free care on the use of primary care becomes larger as the sample is restricted to increasingly sicker (anemic) children.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The results of this study are consistent with Asuming's (2013) findings, which suggested that poorer households have larger unmet needs for health services and are more responsive to interventions. Similarly Powell-Jackson et al (2014) found that the effect of free care on the use of primary care becomes larger as the sample is restricted to increasingly sicker (anemic) children.…”
Section: Resultsmentioning
confidence: 89%
“…Finally, 61 percent of insurance members seek formal medical treatment for their sick children, whereas only 33 percent of nonmembers do so. Yet the children of noninsured mothers do not seem to suffer from a fever or a cough at a different rate, which could be an indication of the absence of moral hazard, as also seen in Powell-Jackson et al (2014).…”
Section: Descriptive Statisticsmentioning
confidence: 89%
“…In total, we have endline data for 2,319 children. Further details of the study – its design, the main outcomes and the findings – are available elsewhere [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%